2021
DOI: 10.1111/apa.16054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nutritional supplementation on growth and body composition in short and lean preadolescent boys: A randomised, double‐blind, placebo‐controlled study

Abstract: Aim To evaluate the effect of nutritional supplementation on height, weight and body composition in short and lean male preadolescents. Methods A randomised, double‐blinded, placebo‐controlled trial of nutritional supplementation of short and lean prepubertal 10–14.5‐year‐old boys. Primary outcomes included Δheight‐SDS and Δweight‐SDS. Secondary outcomes included changes in body composition and BMI‐SDS. Results Of 160 boys enrolled, 126 (80%) completed 6 months’ intervention. Baseline age, height‐SDS, weight‐S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In the extension phase and the 12-month analysis, participants who were good formula consumers managed to maintain their height-SDS score, while the poor formula consumers showed a significant decline in their height-SDS. This result is in line with the positive effect on height-SDS observed in the first phase of the study among the older participants [6].…”
Section: Discussionsupporting
confidence: 88%
“…In the extension phase and the 12-month analysis, participants who were good formula consumers managed to maintain their height-SDS score, while the poor formula consumers showed a significant decline in their height-SDS. This result is in line with the positive effect on height-SDS observed in the first phase of the study among the older participants [6].…”
Section: Discussionsupporting
confidence: 88%
“…Ghosh et al and Alarcon et al suggest that the incidence of upper respiratory tract infections developed over the study period was significantly lower in the ONS + DC group compared to the control group [ 96 , 97 ]. Likewise, the effects of the high-protein ONS diet have also been assessed in healthy short and lean children [ 100 , 101 , 102 ]. Lebenthal et al [ 100 ] evaluated the intake of a high-protein ONS (24.5 g protein/serving) diet for 6 months in 171 short and lean children aged 3–9 years.…”
Section: Optimal Protein Intake In Picky Eatersmentioning
confidence: 99%
“…In the follow-up study, Yackbovitch-Gavan et al [ 101 ] reported similar results, suggesting that a one-year intervention with a high-protein ONS diet was effective in promoting the linear growth of these children, with no change in BMI. In contrast, in a similar approach in short and lean prepubertal boys (10–14.5 y), results reported a change in body composition [ 102 ]. The intervention included two phases: a double-blinded intervention with a high-protein ONS (36 g protein/serving) diet or placebo for 6 months, and subsequently, an open-label, extended 6-month diet containing ONS, for all the participants.…”
Section: Optimal Protein Intake In Picky Eatersmentioning
confidence: 99%
See 2 more Smart Citations